UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Guntoro, Erwanto; Ruqoyyah, Siti (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study aims to describe (1) the use of the Indonesian realistic mathematics approach (PMRI) method by mathematics teachers in learning in class IX B (2) student responses to the use of the PMRI method in mathematics learning in class IX B (3) teacher obstacles that come from students in the use of the PMRI method in mathematics learning in class IXB SMP Negeri 3 Numfor Barat. This study uses a qualitative and quantitative descriptive research design. The subjects of this study are teachers and students. The objects in this study are the use of the PMRI method, student responses, and teacher obstacles. The data collection methods used are the observation method and the interview method. The data in this study were analyzed descriptively quantitatively. The conclusions of this study are (1) the use of the PMRI method has been effective and in accordance with procedures. (2) student responses are mostly positive. (3) the obstacles found by teachers are in terms of students and very limited school facilities. The suggestion of this study is for mathematics teachers to maintain the effectiveness of learning and motivate students more, and for schools to improve learning facilities .